2020
DOI: 10.1007/s00402-020-03433-3
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of two reinforcement rings for primary total hip arthroplasty addressing displaced acetabular fractures: a biomechanical analysis

Abstract: Introduction Aim of this study was to biomechanically compare two different acetabular cup fixation constructs in terms of fracture fixation for displaced acetabular fractures involving the anterior column with hemitransverse fracture under partial and full weight-bearing conditions. Methods Two different reinforcement rings designed as cages for primary THA were biomechanically tested in terms of managing a complex acetabular fracture. Single-leg stance cyclic loading was performed to assess fracture gap move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…There is only one study known to us that used a similar experimental setup and investigated the primary stability of arthroplasty of acetabular fractures with revision cups alone. However, in contrast to our study, no failure test was performed [ 11 ]. Compared to the previous studies, our test setup allows both test variants, a failure test and a cyclic loading test with the anatomically correct force direction while walking.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…There is only one study known to us that used a similar experimental setup and investigated the primary stability of arthroplasty of acetabular fractures with revision cups alone. However, in contrast to our study, no failure test was performed [ 11 ]. Compared to the previous studies, our test setup allows both test variants, a failure test and a cyclic loading test with the anatomically correct force direction while walking.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast to the present study it must be emphasized that not all studies used an experimental set-up with an anatomical force vector in the sense of a single-legged stand [ 11 , 24 , 25 ]. Furthermore, most authors have not tested a full weight bearing or defined it very diversely, which makes it impossible to compare the results [ 25 27 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The key part of the presented procedure is an antiprotrusion ring called ARRP (41medical, Bettlach Switzerland). The ARRP is characterized by a high primary stability allowing for early FWB in almost all cases [ 42 ]. The high primary stability is provided by a high number of 3.5-mm angular stable screws fixed in stable iliac bone (2–4 upper ring screws and 8 screws through the fin).…”
Section: Discussionmentioning
confidence: 99%
“…According to Culemann et al [ 43 ] we used an anterior column with posterior hemitransverse fracture model. In this study, the high primary stability of the ARRP was demonstrated and was significantly higher than that of the Burch Schneider ring [ 42 ].…”
Section: Discussionmentioning
confidence: 99%